Gerakan Pemberdayaan dan Peningkatan Pengetahuan Petugas Fasility Care Sebagai Upaya Penerapan Higiene Dan Sanitasi Lingkungan yang Baik di Kampus FKIK Universitas Jambi - Lesmana S, Oka; Putri, Fitria Eka (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2024)
Environmental sanitation issues in Jambi Province include: the population with access to proper sanitation facilities in 2019 only reached 88.56% of the population in the Jambi Province area, sanitation of public places that meet health requirements only reached 63.11%, and food processing places that meet health requirements are still below 70% of the achievement. Therefore, cross-sector efforts are needed to improve environmental sanitation, but it is also necessary to pay attention to hygiene behavior which is also closely related to sanitation against the occurrence of a disease. The results of the implementation of community service activities in the FKIK Unja campus environment targeting facility care officers are increasing after knowledge about good hygiene and sanitation after socialization. Efforts to form hygienic behavior in the FKIK campus environment have been carried out by empowering officers through the provision of liquid soap for washing hands (CTPS), installing CTPS promotional stickers, and sorting to processing waste. Waste sorting activities have also been carried out by officers using trash bags that have been provided according to the type of waste including organic and inorganic, B3, and waste with economic value.